How knowledge acquisition shapes system understanding in small-scale fisheries - Sina A. Klein (Elsevier, 2021)
Within socio-ecological systems, actors’ interaction with the system may differ greatly, which is likely to result in differences in system understanding. The current work investigated this assumption in the Nile perch fishery at Lake Victoria. Specifically, a survey on Nile perch stock level and the drivers behind stock fluctuations was conducted with 225 participants with formally versus informally acquired knowledge across Kenya, Tanzania, and Uganda. Whereas most participants agreed that the stock has declined, several differences in system understanding were found between types of knowledge acquisition. Specifically, participants with informally acquired knowledge focused on examples of fewer drivers related to tangible human activities (e.g., the use of illegal fishing gear), whilst participants with formally acquired knowledge used more abstract and a larger variety of drivers related to the presence of humans (e.g., overpopulation). These findings confirm that the type of knowledge acquisition affects system understanding in small-scale fisheries and highlights the importance of assessing system understanding of various actors for successful resource management.